MEN AS MOTHERS: THE FILIPINO HOUSEHUSBANDS’ EXPERIENCE - Annabelle B. Francisco; Apolo S. Francisco (Universitas PGRI Madiun, 2022)
This work provides a thick description of how Filipino househusbands take the role switch as mothers. The lived experiences came from fifteen (15) participants captured through face to face interviews and focus group discussion. Five themes emerged; enduring the role switch which covers the difficulties they must face as ‘Moms’ in order to respond to the needs of their children; stabilizing authority and control encompasses how they maintain the stability of their position as the “man” of the house; keeping marital relationship steady describes the struggles they have to endure just to make the marital relationship smooth sailing; withstanding the feelings of guilt, regret and worry illustrates their frustrations and anxiety towards the role switching; and surviving the stigma demonstrates how they handle negative remarks against their masculinity. Though people conclude that they have easy lives, they withstand the pain of being physically away from their wives, seize the abstractness of motherhood and keep their authority and control intact